2017
DOI: 10.1111/imb.12355
|View full text |Cite
|
Sign up to set email alerts
|

Identification and initial characterization of novel neural immediate early genes possibly differentially contributing to foraging‐related learning and memory processes in the honeybee

Abstract: Despite possessing a limited number of neurones compared to vertebrates, honeybees show remarkable learning and memory performance, an example being 'dance communication'. In this phenomenon, foraging honeybees learn the location of a newly discovered food source and transmit the information to nestmates by symbolic abdomen vibrating behaviour, leading to navigation of nestmates to the new food source. As an initial step toward understanding the detailed molecular mechanisms underlying the sophisticated learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…2 , 1-5 , and 2-1 ). This is consistent with previous studies in other insect species ( Kiya et al, 2007 ; Ugajin et al, 2012 , 2016 , 2018 ; Fujita et al, 2013 ). These data indicate that, in general, mRNAs of insect neuronal IEGs show slower expression kinetics than those in the vertebrate systems.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…2 , 1-5 , and 2-1 ). This is consistent with previous studies in other insect species ( Kiya et al, 2007 ; Ugajin et al, 2012 , 2016 , 2018 ; Fujita et al, 2013 ). These data indicate that, in general, mRNAs of insect neuronal IEGs show slower expression kinetics than those in the vertebrate systems.…”
Section: Discussionsupporting
confidence: 94%
“…Although the activity-regulated genes or neuronal IEGs have not been identified in any hemimetabolous insects including the cricket, recent genome-wide analyses of activity-regulated genes in vertebrates ( Nedivi et al, 1993 ; Matsuo et al, 2000 ; Wada et al, 2006 ; Spiegel et al, 2014 ) and several insect species ( Guan et al, 2005 ; Chen et al, 2016 ; Ugajin et al, 2018 ) highlighted evolutionarily conserved transcription factor IEGs. On the basis of previous reports, we selected four transcription factor genes as our candidates for activity-regulated genes in the cricket as follows: fos-related antigen ( fra ; c-fos homolog), jun-related antigen ( jra ; c-jun homolog), early growth response ( egr ; egr-1/zif268/NGFI-A homolog), and hormone receptor 38 ( hr38 ; NGFI-B/nur77/NR4A1 homolog).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies, however, reported that, in the silk moth and fruit fly, HR38 is an immediate early gene, whose neuronal expression is activated by neuronal excitation (Fujita et al, 2013 ), and that HR38 expression in the honeybee brain is induced by foraging behavior (Ugajin et al, 2018 ). These results suggest an alternative possibility that HR38 expression in the sKCs of the honeybee brain is a consequence of the foraging behavior, and does not necessarily represent a gene expression profile specific to the forager brain.…”
Section: Unique Gene/protein Expression Profiles Of Kc Subtypes In Thmentioning
confidence: 99%
“…Since detection of neural activity using immediate early genes revealed that MB KCs (Singh et al, 2018 ; Ugajin et al, 2018 ), especially sKCs and some mKCs (Kaneko et al, 2013 ), are active in the brains of foragers, it is plausible that these KC subtypes are related to sensory information processing during the foraging flights.…”
Section: Unique Gene/protein Expression Profiles Of Kc Subtypes In Thmentioning
confidence: 99%
“…Activation of IEGs or genes regulated by them were compared between different pupal and adult stages [89, 90], and between individuals performing different tasks like nursing the brood, dancing to communicate a novel food source to nestmates, and foraging for nectar or pollen [91, 92]. Behavioral approaches aiming to stimulate IEG expression in honey bees included more general stimulation like seizures induced by awakening from anesthesia [9295], exposure to light [96] or plant and pheromonal odors [9698], and sucrose feeding (food reward stimulation; [99]). In addition, more specific behaviors were correlated with IEG expression, for example, feeding of sucrose or pollen of different qualities [100], as well as different aspects of orientation flights [92, 95, 101] and foraging activity [102, 103].…”
Section: The Honey Bee: Insect Model For Monitoring Ieg Expressionmentioning
confidence: 99%